Pembaharuan Hukum Islam - Nurhuda, Rohmad (Institut Agama Islam Negeri Ponorogo, 2022)
Noel J. Coulson identifies four distinct historical manifestations of the rise of Islamic law: first, the incorporation of the siyasa doctrine, which required the codification (grouping of similar laws into legal books) of Islamic law into state statutes. Second, Muslims are not required to follow a particular madhhab; this is what he calls the doctrine of superstition (selection), which determines which schools of thought are most widely accepted. As a third point,